ANALISIS KESULITAN BELAJAR DI MASA PEMBELAJARAN JARAK JAUH (PJJ) SMP SWASTA NAHDLATUL ULAMA T.A 2021 / 2022 - Suharsih; Hendri Irawan (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2021)
This research is titled “Analysis of Learning Difficulties during Distance Learning (PJJ) at Nahdlatul Ulama Private Middle School, Academic Year 2021/2022.” The background of this study is the outbreak of the Covid-19 virus, which necessitated schools in Indonesia, including Nahdlatul Ulama Private Middle School, to implement distance learning (PJJ). Consequently, the researcher aims to analyze the types and nature of learning difficulties encountered during the implementation of PJJ. The purpose of this study is to identify the learning difficulties at Nahdlatul Ulama Private Middle School and understand the factors influencing these difficulties. This research employs a qualitative approach, with data collected through observations, interviews with teachers, students, and parents, as well as documentation. The findings reveal various learning difficulties experienced during PJJ and identify both internal and external factors contributing to these challenges. Internal factors arise from within the individuals involved in the teaching and learning process, such as teachers and students, while external factors include the learning environment, such as school, family, and community settings.